Development of Physiotherapy Standard Operating Procedures for Tennis Elbow Cases in Badminton Players - Niken Hertiana Wulandari; Totok Budi Santoso (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The hand is one of the limbs that is most often used in various daily activities. Excessive hand and wrist activity if prolonged can cause a problem. Problems caused by excessive activity can cause injury. Tennis elbow is one of the injuries also called the lateral epicondylus, this injury occurs due to excessive use of extensor muscles (overuse) resulting in inflammation (inflammation) of the extensor carpi radialis brevis tendon. Usually this injury occurs in tennis players, badminton and various jobs that dominantly use the wrist. Physiotherapy as one of the implementers of health services that play a role and are responsible for improving health status, physiotherapy is a form of health service aimed at individuals and / or groups to develop, maintain and restore motion and body function throughout the life span by using manual handling, motion enhancement, equipment (physical, electrotherapeutic and mechanical). To develop Standard Operating Procedures in performing physiotherapy treatment in cases of tennis elbow. This research was conducted using the research method of developing physiotherapy operational standards with this model of handling injuries to tennis elbow starting from preliminary studies, history taking, assessment, diagnosis, intervention and evaluation. The type of research conducted is quantitative research using quasi experimental methods with pretest-posttest control group design. The experimental group and control group did an initial test. Both groups received different treatments, where the experimental group received thrust manipulation intervention and the control group received non thrust intervention in the form of deep transverse friction. There is a decrease in pain after the thrust and nonthrust method manipulation therapy in both groups as measured using the Numeric Rating Scale (NRS), after being evaluated for two weeks it is known that the pain does not increase. The action of thrust and nonthrust manipulation therapy is recommended for the treatment of pain in tennis elbow injuries. However, between these two methods does not yet exist. There is no significant difference between these two methods given the time constraints of the study.